Pengaruh FDI, Ekspor, dan Pengguna Internet terhadap Pendapatan Industri Video Game Lima Negara ASEAN - I Kadek Ardita Mahendra; I Nyoman Wahyu Widiana (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The video game industry has grown into one of the most dynamic pillars of the digital economy in the ASEAN region, driven by technological acceleration and economic factors that also influence the development of this industry. This study aims to analyze the influence of foreign direct investment (FDI), exports, and internet users on the revenue of the video game industry in five ASEAN countries during the period 2013-2023. The data used is 11 years of time series data obtained from Statista, New Zoo, and the World Bank. Panel data regression was used to test the relationship between these variables and the revenue of the video game industry in the ASEAN region. The results show that simultaneously, FDI, exports, and internet users have a significant effect on the revenue of the video game industry in five ASEAN countries. Partially, FDI has a negative and significant effect on the revenue of the video game industry in five ASEAN countries. Meanwhile, exports and internet users have a positive and significant effect. These findings indicate that an increase in exports and internet users plays an important role in driving an increase in the video game industry revenue of the five ASEAN countries. Meanwhile, an increase in FDI hinders the video game industry revenue of the five ASEAN countries. Therefore, policymakers and industry players should focus more on strengthening the local IP export ecosystem and equalizing digital infrastructure, as well as formulating strategies to attract FDI.